Chronic Leg Ulcers: Epidemiology, Aetiopathogenesis, and Management. (22nd April 2013) - Agale, Shubhangi Vinayak
Abstract : Chronic leg ulcer is defined as a defect in the skin below the level of knee persisting for more than six weeks and shows no tendency to heal after three or more months. Chronic ulceration of the lower legs is a relatively common condition amongst adults, one that causes pain and social distress. The condition affects 1% of the adult population and 3.6% of people older than 65 years. Leg ulcers are debilitating and greatly reduce patients' quality of life. The common causes are venous disease, arterial disease, and neuropathy. Less common causes are metabolic disorders, hematological disorders, and infective diseases. As many factors lead to chronic lower leg ulceration, an interdisciplinary approach to the systematic assessment of the patient is required, in order to ascertain the pathogenesis, definitive diagnosis, and optimal treatment. A correct diagnosis is essential to avoid inappropriate treatment that may cause deterioration of the wound, delay wound healing, or harm the patient. The researchers are inventing newer modalities of treatments for patients with chronic leg ulceration, so that they can have better quality life and reduction in personal financial burden.